Design and development of a 100 W Proton exchange membrane fuel cell uninterruptible power supply - Du Toit, Johannes Paulus (My University, 2006)
This study presents the design of a proton exchange membrane fuel cell stack that can be used to replace conventional sources of electrical energy in an uninterruptible power supply system, specifically for use in the telecommunications industry. One of the major concerns regarding the widespread commercialization of fuel cells is the high cost associated with fuel cell components and their manufacturing. A fuel cell design is presented in which existing, low-cost, technologies are used in the manufacture of cell components. For example, printed circuit boards are used in the manufacturing of bipolar flow plates to significantly reduce the cost of fuel cells. The first objective was to design, construct and test a single fuel cell and small fuel cell stack in order to evaluate the use of printed circuit boards in bipolar plate manufacturing. Since the use of copper in a fuel cell environment was found to reduce the lifetime of the cells, the bipolar plates were coated with a protective layer of nickel and chrome. These coatings proved to increase the lifetime of the cells significantly. Power outputs of more than 4 W per cell were achieved. The second objective was to analyze a small fuel cell stack in order to obtain a model for predicting the performance of larger stacks. A mathematical model was developed which was then used to design an electronic circuit equivalent of a fuel cell stack. Both models were adapted to predict the performance of a fuel cell stack containing any number of cells. The models were proven to be able to accurately predict the performance of a fuel cell stack by comparing simulated results with practical performance data. Finally, the circuit equivalent of a fuel cell stack was used to evaluate the capability of a switch mode boost converter to maintain a constant voltage when driven by a fuel cell stack, even under varying load conditions. Simulation results showed the ability of the boost converter to maintain a constant output voltage. The use of supercapacitors as a replacement for batteries as a secondary energy source was also evaluated.
M. Tech. (Engineering Department Applied Electronics and Electronic Communication, Faculty of Engineering) Vaal University of Technology
Keywords: Proton exchange membrane fuel stack; Power supply systems; Telecommunications industry; Fuel cells; 621.312429; Fuel cells; Renewable energy sources